Cost-effectiveness of entecavir versus adefovir for the treatment of chronic hepatitis B in patients with decompensated cirrhosis from a third-party US payer perspective - Tsai N; Jeffers L; Cragin L; Sorensen S; Su W; Rosenblatt L; Tang H; Hebden T; Juday T (Dove Medical Press, 2012)
Naoky Tsai,1 Lennox Jeffers,2 Lael Cragin,3 Sonja Sorensen,3 Wenqing Su,3 Lisa Rosenblatt,4 Hong Tang,4 Tony Hebden,4 Timothy Juday41John A Burns School of Medicine, University of Hawaii, Honolulu, HI, USA; 2University of Miami School of Medicine, Miami, FL, USA; 3United BioSource Corporation, Bethesda, MD, USA; 4Bristol-Myers Squibb Company, Plainsboro, NJ, USABackground: Decompensated cirrhosis is a serious clinical complication of chronic hepatitis B (CHB) that places a large economic burden on the US health care system. Although entecavir has been shown to improve health outcomes in a cost-effective manner in mixed populations of CHB patients, the cost-effectiveness of entecavir has not been evaluated in CHB patients with decompensated cirrhosis.Methods: This study assessed the cost-effectiveness of entecavir versus adefovir, from a US payer perspective, in CHB patients with decompensated cirrhosis, using a health-state transition Markov model with four health states: hepatocellular carcinoma (HCC), HCC-free survival, post-liver transplant, and death. The model considered a hypothetical patient population similar to that included in a randomized controlled trial in the target population (ETV-048): predominantly male (74%), Asian (54%), mean age 52 years, hepatic decompensation (Child–Pugh score ≥ seven), hepatitis B e antigen-positive or -negative, treatment-naïve or lamivudine-experienced, and no liver transplant history. Clinical inputs were based on cumulative safety results for ETV-048 and published literature. Costs were obtained from published literature. Costs and outcomes were discounted at 3% per annum.Results: For 1000 patients over a 3-year time horizon, predicted overall survival and HCC-free survival were longer with entecavir than with adefovir (2.35 versus 2.30 years and 2.11 versus 2.03 years, respectively). Predicted total health care costs were $889 lower with entecavir than with adefovir ($91,878 versus $92,768). For incremental cost/life-year gained and incremental cost/HCC-free-year gained, entecavir was less costly and more effective than adefovir. Sensitivity analyses found the results to be robust to plausible variations in health-state costs and discount rate.Conclusion: This analysis suggests that entecavir improves survival outcomes in a cost-saving manner compared with adefovir in CHB patients with hepatic decompensation.Keywords: hepatocellular carcinoma, antiviral, survival, health economics, incremental net benefit